The influence of the attractiveness of context of a mathematical word problem on solving processes - Havlíčková, Radka (Scientia in educatione, 2020)
Research on mathematical word problems suggests that differences in success are not only due to different levels of pupils’ cognitive abilities but that their motivation plays a role, too. Therefore, in this study, we focused on the context as a non-mathematical parameter of word problems and investigated its influence on pupils’ success in solving the problems. We focused on the potential attractiveness of the context and investigated whether pupils would be more successful in solving word problems with elements of fairy tale, science fiction or humour than in the case of similar problems with the same structure but with a neutral context. Pupils of the 5th and 6th grades of primary school (n5 = 623, n6 = 291) were divided into two groups of a comparable ability and each was presented with one of the variants – either attractive or neutral. To evaluate the results quantitatively, we used the Item Response Theory which allowed us to determine the difficulty of the task depending on the latent abilities of pupils and enabled us to assess the discriminating properties of the problems. In the qualitative part of the study, we investigated the differences between pupils in terms of their solving strategies and errors. It was established that the attractive context could, under certain conditions, stimulate the pupils’ efforts towards solving the problems and, in some cases, can slightly improve the success rate. The study also showed that when varying the context, it is difficult to keep the other parameters of the problem without changes, possibly influencing the complexity of the situational model, and pointed out inconsistencies in some research results.